Pharmacological Neuroenhancement in the Field of Economics—Poll Results from an Online Survey - Dietz, Pavel; Soyka, Michael; Franke, Andreas G. (Frontiers in Psychology, 2016)
Introduction: The use of over-the-counter, prescription, and illicit drugs to increase attention, concentration or memory – often called (pharmacological) neuroenhancement – shows a broad range of prevalence rates among students. However, very little data is available on neuroenhancement among employed persons. The aim of this study was to provide first data on substance use for neuroenhancement among readers of the German “Handelsblatt” coming from the field of economics. Methods: Readers of the online edition of the Handelsblatt, a leading print and online medium for the field of economics, were invited to participate in a survey via a link on the journal homepage to complete a web-based questionnaire. Within the questionnaire, participants were asked for their gender, current age, current professional status, hours of work per week, prevalence rates of substance use for the purpose of neuroenhancement as well as for reasons of its use. Binary regression analyses with stepwise forward selection were used to predict the dependent variables “use of illicit and prescription drugs for neuroenhancement” (yes/no), “use of over-the-counter drugs for neuroenhancement” (yes/no), and “use of any drug for neuroenhancement” (yes/no). Results: A total of 1,021 participants completed the anonymous survey. Lifetime prevalence for the use of any drug for neuroenhancement was 88.0% and for the use of illicit and prescription drugs for neuroenhancement 19.0%. Reasons and situations that predicted neuroenhancement with illicit and prescription drugs were “curiosity”, “to enhance mood”, ”for a confident appearance”, “stress/pressure to perform”, and “deadline pressure”. Discussion: The study shows that neuroenhancement with drugs is a widespread and frequent phenomenon among people belonging to the professional field of economics. Given in the literature that the use of drugs, especially prescription and illicit drugs, may be associated with side effects, the high epidemic of drug use for neuroenhancement also shown in the present paper underlines the new public health concern of neuroenhancement.